SII@EDU social innovation initiatives: HURES X ETSA: English Fun Day 2019 / Munirah Mohd Izam and Wan Nurul Elia Haslee Sharil - Mohd Izam, Munirah; Haslee Sharil, Wan Nurul Elia (Galeri Seni Tuanku Nur Zahirah (GESTURZ), Universiti Teknologi MARA in collaboration with Faculty of Education (EDU), Universiti Teknologi MARA, Shah Alam, 2020)
HURES X ETSA: English Fun Day 2019 is a one-day community service engagement programme with the residents of Asrama Damai, Kuang, Selangor. The programme was enabled by a collaboration between two inter-faculty student societies; HURES and ETSA of UiTM Cawangan Selangor, Kampus Puncak Alam.